2021
DOI: 10.3390/buildings11080362
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Product Declarations of Structural Wood: A Review of Impacts and Potential Pitfalls for Practice

Abstract: The use of wood and timber products in the construction of buildings is repeatedly pointed towards as a mean for lowering the environmental footprint. With several countries preparing regulation for life cycle assessment of buildings, practitioners from industry will presumably look to the pool of data on wood products found in environmental product declarations (EPDs). However, the EPDs may vary broadly in terms of reporting and results. This study provides a comprehensive review of 81 third-party verified EN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Another method is the -1/+1 approach that account the sequestered carbon in wood materials as a negative impact during construction and consider it fully released at the EoL [5]. At times, the EoL is left out of Environmental Product Declarations of wooden building materials [8], consequently the release is not accounted in the -1/+1 approach and the wooden building material emerge as more climate friendly than it might be.…”
Section: Biogenic Carbon Methodsmentioning
confidence: 99%
“…Another method is the -1/+1 approach that account the sequestered carbon in wood materials as a negative impact during construction and consider it fully released at the EoL [5]. At times, the EoL is left out of Environmental Product Declarations of wooden building materials [8], consequently the release is not accounted in the -1/+1 approach and the wooden building material emerge as more climate friendly than it might be.…”
Section: Biogenic Carbon Methodsmentioning
confidence: 99%
“…Anderson & Moncaster, (2020) also reviewed the embodied carbon (A1-A3) of in-situ concretes reported in EPD but did not consider their energy use. Rasmussen et al, (2021) reviewed the correlation between embodied carbon (A1-A3) and the total use of renewable primary energy (PERT), and of non-renewable primary energy (PENRT) as reported in EPD for structural timber products (cross laminated timber (CLT), glulam, laminated veneer lumber (LVL) and sawn timber). Rasmussen et al found only a low correlation (R 2 ) between embodied carbon and PERT (0.0192), and embodied carbon and PENRT (0.1162), they did not explore the correlation with PERE (renewable primary energy used as energy, so excluding the energy content of the actual timber itself) nor with the total energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Rasmussen et al conducted a comprehensive review of the EPDs of structural woods in which they analysed 81 EPDs across several countries. They found that the investigated EPDs had varied values (up to 90% uncertainty for GWP), which were caused by different specificities such as manufacturer, facility, co-production, time of data representation, and supply chain [54]. Janjua et al investigated the effect of service life on a building's environmental performance.…”
Section: Introductionmentioning
confidence: 99%